Pesan pendidikan kisah Qabil dan Habil: Mengungkap makna ikhlas perspektif Al-Qur’an - Arisanti, Kustiana (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2024)
The Qur'an is a source of inspiration for the life of Muslims. It contains several values and guidelines that can be used as references in the fields of religion, social life, economics and education. The teachings of the Qur'an are packaged in such a way and delivered variably. Some are in the form of information, government and prohibitions, some are modified in the form of descriptions of stories. One of the interesting stories to study is the story of Qabil and Habil, which not only tells the story of the first murder committed, but more than that. The story of Qabil and Habil leaves moral education values that are full of values and meanings. Among these values is the value of sincerity and surrender to the Creator. To describe these educational values, this research uses descriptive qualitative research, with a literature approach because the main data sources in this research are books, classical books and scientific articles. Based on the stories of Qabil and Habil, the value of sincerity found is “doing something lillah” or because of Allah. In addition, discussing the story of Qabil and Habil, this study also describes the munasabah between verses and also explains the meaning of sincerity based on the words described in the Qur'an, such as sincerity contains the meaning of pure, clean from dirt, specialization and many more descriptions of the meaning of sincerity interpreted from the word “sincerity” in the Qur'an.